Image analysis as a tool to predict washout in sludge bed reactors through the quantification of microbial filamentous structures - Alves, M. M. (2004)
Image analysis techniques are applied to monitor the morphological changes in granular sludge, present in an EGSB reactor fed with oleic acid. Deterioration of granular sludge was monitored along the trial period by measuring the percentage of aggregates smaller than 1 mm (in terms of Feret diameter) either using the projected area or the number of aggregates. The ratio of total filaments length to cross-sectional area of aggregates defined as LfA, was applied to quantify the dispersion level of the granular sludge. LfA was sensitive to the sludge deterioration process and was able to indicate, with the anticipation of about 1 month, the most significant biomass washout episode that occurred in the trial period. A mechanism of filaments release, detachment and selective washout was proposed to explain the action of LfA from this viewpoint.